Analysis the Effect of Physical Parameters on Groundwater Salinity in the KEK Mandalika Lombok - Alaydrus, Alfina Taurida; Susilo, Adi; Minardi, Suhayat; Naba, Agus; Wahid, Agus (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
KEK Mandalika is located in a coastal area which is very vulnerable to changes in the quantity and quality of groundwater due to seawater intrusion. This study aims to detect the presence of aquifers (groundwater), seawater intrusion and analyze the effect of physical parameters to determine groundwater quality in the KEK Mandalika area. The physical parameters used are: resistivity, conductivity, Total Dissolved Solid (TDS) and salinity. The resistivity value was obtained using the geoelectric resistivity method with 10 lines using a dipole-dipole configuration, while the other parameters were obtained through 10 samples of well water which were located adjacent to the geoelectric line. Resistivity geoelectrical data processing using Res2Dinv software, Surfer13 software to observe the spread of each parameter and perform regression analysis to see the effect of resistivity, conductivity, TDS on salinity. The results obtained are geoelectric resistivity in the form of an aquifer layer around the KEK Mandalika at a depth of (2 – 12) meters with resistivity values ranging from (0 – 2257) Ωm. The results of groundwater samples are: conductivity with values ranging from (1.02 – 20) mS/cm, TDS with values ranging from (67.3 – 3070) mg/L and salinity with values ranging from (0.05 – 2.07) ppt. The effect of conductivity, TDS on salinity is directly proportional, while the effect of resistivity on salinity is inversely proportional. Most of the KEK Mandalika area is likely to experience seawater intrusion, especially in the Eastern region.